HIV/AIDS, comorbidity, and alcohol: can we make a difference? - Justice, Amy; Sullivan, Lynn; Fiellin, David (Alcohol research & health : the journal of the National Institute on Alcohol Abuse and Alcoholism, 2010)
Alcohol use is common among people infected with HIV and plays an important role in their health outcomes. Because alcohol use complicates HIV infection and contributes to comorbid diseases, it is important for researchers and practitioners to understand these interactions and to integrate alcohol treatment with medical management of long-term HIV infection and associated comorbidity. The Veterans Aging Cohort Study (VACS) is a large, multisite study of the effects of alcohol use on HIV outcomes in the broader context of aging. A multilevel strategy intervention trial is needed to address the many modifiable implications of alcohol consumption among those receiving treatment for HIV.
Keywords: Acquired Immunodeficiency Syndrome; Alcohol Drinking; Animals; Comorbidity; HIV Infections; Humans; Multicenter Studies as Topic